Transformation of Knowledge and Skills in Agriculture Business Through Clean Air Agriculture Training of Trainers (Case Study of Clean Air Agriculture Training of Trainers PT. CMI) - Setyoko, Heru; Ariyanto, Sigid (Edumedia Solution, 2025)
Transformation of Knowledge and Skills through Clean Air Agriculture Training of Trainers was carried out to prepare Village Facilitators/Village Companions/Village Environmental Heroes in 10 villages in Sanggau Regency, West Kalimantan. The impact of Training of Trainers (ToT) on increasing participants' knowledge and skills related to Clean Air Agriculture techniques and Community Organizing Management was evaluated using the Mix-Method method. Quantitative data were collected participatorily using a questionnaire after the training, the assessment used a score of 1-10. Qualitative data were collected through interviews with ToT participants after the training, and the data were processed descriptively. The results of the Training of Trainers had a significant impact, on knowledge of Clean Air Agriculture Techniques increasing by 68.2% and knowledge and skills of community facilitation and community organizing increasing by 55.4%. Training of Trainers with an adult education method and learning experience, can involve full participant participation, and can transform the knowledge and technical skills of Clean Air Agriculture and Community Organizing effectively.Keywords: Management, Agriculture, clean air Agriculture, no-burn Agriculture,